A sustentabilidade dos loteamentos Picollo, Wurzius e Cidade Campo III da cidade de Pato Branco, criados a partir do Plano Diretor de 2008 - Silverio, Guilherme Sebastião (2013)
The growth of cities has become a major concern of modern society. Cities have grown and with it the problems of this reality have advanced. Therefore urban planning should receive strong concern in municipal diaries, academic and government spheres. The aim of this paper is to discuss the way the land occupation in Pato Branco had happened in urban dimension in order to get in a short way the history of the beginning of colonization. Also to discuss the urban structure occupation, using data from IPPUPB - Information, Research and Urban Planning Department of Pato Branco. Drawing a parallel between the federal law 10.257 about City Statute and the municipal law 28 that created the Pato Branco Master Plan and also the complementary law 46 about use and land occupation. This paper deals the city planning importance, the urban planning from the point of view of sustainability. And fundamentally studying three allotments of Pato Branco city - Piccolo, Cidade Campo III - Wurzius - using sustainability indicators in order to measure dimensions of quality and service of the relevant legislation, specifically after the Master Plan 2008.